Nitrogen immobilization in paddy soils as affected by redox conditions and rice straw incorporation - Said-Pullicino, Daniel; Cucu, Maria Alexandra; Sodano, Marcella; Birk, Jago Jonathan; Glaser, Bruno; Celi, Luisella (Geoderma, 2014)
Biotic and abiotic processes controlling nitrogen (N) immobilization in paddy soils may significantly affect nutrient availability for plant uptake during the rice cropping season, as well as the efficiency of applied N fertilizers. Understanding the influence of water and crop residue management practices on N availability, however, requires detailed insight into the mechanisms and factors controlling N immobilization in these soils. We evaluated changes in fertilizer-15N immobilization in a paddy topsoil incubated for 160d under flooded or non-flooded conditions, with or without rice straw incorporation. The distribution of immobilized N between different soil fractions and interlayer N fixation was assessed by combining aggregate-size, density and chemical fractionation with stable isotope analysis, while compound-specific δ15N analysis of individual amino sugars was used to evaluate microbial utilization of applied N. Fast immobilization of applied N (≈48% applied N) was observed in both flooded (Eh=+0.4 to −0.2V) and non-flooded (Eh=+0.4 to +0.6V) soils, however in the latter most of this N was released during incubation. The finer soil fractions served as the greatest sink of immobilized N, retaining 5–36% of the added N. Although biotic processes were mainly responsible for N retention, about 4–11% of N applied to flooded soils was weakly fixed within the interlayer of clay minerals, primarily associated with microaggregates. Straw addition further enhanced N immobilization under both oxic and anoxic conditions, with ≈12% of total immobilized N (2–4% of applied N) associated with the light organic matter fraction. The increasing incorporation of applied N into microbial residues suggested that addition of rice straw to paddy soils may lead to effective microbial-mediated immobilization and stabilization of significant portions of N inputs. •More fertilizer-N is immobilized under anoxic with respect to oxic soil conditions.•Finer soil fractions serve as the greatest sink of immobilized N.•Flooding influences aggregate stability and N immobilization mechanisms.•Microbial N immobilization is intimately coupled with crop residue incorporation.•Interlayer NH4+ fixation depends on redox conditions and straw incorporation.